2017
DOI: 10.1093/nar/gkx1007
|View full text |Cite
|
Sign up to set email alerts
|

FnCpf1: a novel and efficient genome editing tool for Saccharomyces cerevisiae

Abstract: Cpf1 is a new class II family of CRISPR-Cas RNA-programmable endonucleases with unique features that make it a very attractive alternative or complement to Cas9 for genome engineering. Using constitutively expressed Cpf1 from Francisella novicida, the present study demonstrates that FnCpf1 can mediate RNA-guided DNA cleavage at targeted genomic loci in the popular model and industrial yeast Saccharomyces cerevisiae. FnCpf1 very efficiently and precisely promoted repair DNA recombination with efficiencies up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 64 publications
(95 reference statements)
4
150
1
Order By: Relevance
“…Instead of G-rich PAMs required by Cas9, Cas12a recognizes T-rich PAMs and thus further increases the number of potential target sites. Recent publications in yeast and rice have revealed that a PAM of 5 0 -TTTV-3 0 is also strongly preferred by FnCas12a [69,70]. In contrast to Cas9 which generates bluntended DSBs proximal to the PAM, Cas12a generates staggered DSBs distal from the PAM.…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of G-rich PAMs required by Cas9, Cas12a recognizes T-rich PAMs and thus further increases the number of potential target sites. Recent publications in yeast and rice have revealed that a PAM of 5 0 -TTTV-3 0 is also strongly preferred by FnCas12a [69,70]. In contrast to Cas9 which generates bluntended DSBs proximal to the PAM, Cas12a generates staggered DSBs distal from the PAM.…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…The Cas12a orthologues recognize T-rich PAMs, which are 5 0 -TTV(A/C/ G)-3 0 for FnCas12a and 5 0 -TTTV-3 0 for AsCas12a and LbCas12a, although 5 0 -TTN-3 0 and 5 0 -TTTN-3 0 can also be recognized at lower efficiency [68]. Recent publications in yeast and rice have revealed that a PAM of 5 0 -TTTV-3 0 is also strongly preferred by FnCas12a [69,70]. Recently, the targeting range for Cas12a has been expanded greatly by engineered versions that recognize 5 0 -TYCV-3 0 and 5 0 -TATV-3 0 PAMs without sacrificing efficiency or specificity [71].…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…However, the current CRISPR/ Cas9-based multiplex genome editing tool for P. patens typically requires simultaneous delivery of multiple gRNA plasmids (Lopez-Obando et al, 2016;Nomura et al, 2016), making it complex and time-consuming for plasmid construction. Although Cas12a-mediated gene editing has been intensively studied in several plant species such as rice (Kim et al, 2016;Zetsche et al, 2016;Hu et al, 2017;Swiat et al, 2017;Tang et al, 2017;Wang et al, 2017;Ding et al, 2018;Li et al, 2018b), this technique has not previously been employed in moss. Since the efficiency of gene targeting by Cas12a varies from species to species (Tang et al, 2017;Lee et al, 2018), the CRISPR/Cas12a system requires further optimization.…”
Section: Introductionmentioning
confidence: 99%
“…However, a later study demonstrated that to achieve high cleavage activity in human cells, FnCpf1 requires a PAM defined as 5’‐YTV‐3’ (Y represents C or T, and V represents A, C or G), and the spacer sequence with a length of 21 nt, rather than the commonly used 23‐25 nt, could lead to maximal editing (Tu et al ). Another study further showed that FnCpf1 preferred the TTTV motif to cleave target DNA when expressed in Saccharomyces cerevisiae (Świat et al ). Based on these reports, we modified some of the guides and cloned the array into the TCTU expression cassette, together with hammerhead and HDV ribozyme (Figure A; Table S2).…”
mentioning
confidence: 99%